1961
DOI: 10.1021/jo01061a001
|View full text |Cite
|
Sign up to set email alerts
|

7-Substituted Norbornadienes1

Abstract: Several 7-norbomadienyl derivatives have been synthesized utilizing the reaction of norbornadiene and t-butyl perbenzoate. In addition, an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
3

Year Published

1969
1969
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 0 publications
0
48
0
3
Order By: Relevance
“…The synthesis of our required substrates was, for the most part, possible through the application of known protocols from the literature. [14] It was found that starting from commercially available NBD 1a allowed access to the desired substrates as shown in Scheme 1. The synthesis of these materials proceeded smoothly in most cases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of our required substrates was, for the most part, possible through the application of known protocols from the literature. [14] It was found that starting from commercially available NBD 1a allowed access to the desired substrates as shown in Scheme 1. The synthesis of these materials proceeded smoothly in most cases.…”
Section: Resultsmentioning
confidence: 99%
“…The solvents were purified by distillation under dry nitrogen, from CaH 2 (Et 3 N) and from potassium/benzophenone (THF). The 7-substituted norbornadienes 1b-c, [14] Cp*RuCl(COD) [21] and the alkyne 4 [22] were prepared according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] A one-pot synthesis has been developed for a high-yield conversion of [Mo(NtBuAr) 3 ] into its methylidyne counterpart (Scheme 2). [5] In this methine (CH) transfer reaction, 7-chloronorbornadiene [25][26][27] is used as the methine source, while the three-coordinate titanium(iii) complex [Ti(NtBuAr) 3 ] is used as a specific chlorine-atom abstractor. It is well documented that [Ti(NtBuAr) 3 ] is potent for the one-electron reduction of metal oxo groups, [28,29] carbonyl groups, [30] metalhalogen bonds, [31] and carbon-halogen bonds.…”
Section: Terminal Carbide Complexes: Methine Groupmentioning
confidence: 99%
“…This process again capitalizes on the Curtin-Hammett energy profile of the system, only this time in the opposite direction to advance 10 through sigmatropic rearrangement and reduction. The hydroxy group in 20 underwent substitution with chloride resulting in net retention of configuration at C17, presumably as a result of π-bond anchimeric assistance, [37] to afford the chloride 21 (97% yield, over 2 steps), which constitutes the C17 epimer of 14 (see Scheme 4).…”
mentioning
confidence: 99%